Kinetics Modeling on the Biosorption of Remazol Black B Dye by Aspergillus flavus - Yahuza, Salihu; Sabo, Ibrahim Alhaji; Biu, Hadiza Aliyu (Journal of Environmental Microbiology and Toxicology, 2021)
Azo dyes, such as Remazol Black B, are different from conventional dyes in that they establish covalent bonds with textile fibers like cotton. They are widely utilized in the textile industry because of their favorable properties of bright color, water resistance, simple application procedures, and low energy consumption. Their discharge into receiving streams has major environmental consequences, such as reducing photosynthesis in aquatic life due to lower light penetration. The biosorption isotherm data of Remazol Black B dye biosorption by Aspergillus flavus were investigated using two models—pseudo-1st order and pseudo-2nd order—and fitted using non-linear regression. The pseudo-1st order model was found to be the best by statistical analysis using root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), accuracy factor (AF), corrected AICc (Akaike Information Criterion), Bayesian Information Criterion (BIC), and Hannan–Quinn information criterion (HQC). At 250 mg/L, kinetic analysis using the pseudo-1st order model yielded an equilibrium sorption capacity qe of 4.61 mg/g (95 % confidence interval from 4.54 to 4.68) and a pseudo-1st-order rate constant, k1 of 0.15 (95% C.I. from 0.128 to 0.164).